Production of pectinase by solid-state fermentation with Penicillium viridicatum RFC3 - Silva, D.; Tokuioshi, K.; Martins, E. D.; Da Silva, R.; Gomes, E. (Elsevier B.V., 2005)
Endo-polygalacturonase (endo-PG), exo-polygalacturonase (exo-PG) and pectin liase (PL) were produced by solid-state fermentation of a mixture of orange bagasse and wheat bran (1:1) with the filamentous fungus Penicillium viridicatum RFC3. This substrate was prepared with two moisture contents, 70% and 80%, and each was fermented in two types of container, Erlenmeyer flask and polypropylene pack. When Erlenmeyer flasks were used, the medium containing 80% of initial moisture afforded higher PL production while neither exo- nor endo-PG production was influenced by substrate moisture. The highest enzyme activities obtained were 0.70 U mL(-1) for endo-PG, 8.90 U mL(-1) for exo-PG, and 41.30 U mL(-1) for PL. However, when the fermentation was done in polypropylene packs, higher production of all three enzymes was obtained at 70% moisture (0.7 and 8.33 U mL(-1) for endo- and exo-PG and 100 U mL(-1) for PL). An increase in the pH and decrease in the reducing sugar content of the medium was observed. The fungus was able to produce pectin esterase and other depolymerizing enzymes such as xylanase, CMCase, protease and amylase. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: pectinase; solid-state fermentation; Penicillium viridicatum; orange bagasse